2006
DOI: 10.1158/0008-5472.can-05-2090
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell–Derived Dendritic Cells Expressing Glypican-3, a Recently Identified Oncofetal Antigen, Induce Protective Immunity against Highly Metastatic Mouse Melanoma, B16-F10

Abstract: We have recently established a method to generate dendritic cells from mouse embryonic stem cells. By introducing exogenous genes into embryonic stem cells and subsequently inducing differentiation to dendritic cells (ES-DC), we can now readily generate transfectant ES-DC expressing the transgenes. A previous study revealed that the transfer of genetically modified ES-DC expressing a model antigen, ovalbumin, protected the recipient mice from a challenge with an ovalbumin-expressing tumor. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…This total was estimated to be at least 160 times more than that of the MC-DCs (without c-Myc transduction). Surface phenotype of PSC-derived cells in the stages of MCs and pMCs The myeloid cells (days [13][14] were a heterogeneous population, almost 90% of which was characterized to be CD11b þ ( Fig. 2A) (Fig.…”
Section: Generation Of Pmcs From Mouse Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…This total was estimated to be at least 160 times more than that of the MC-DCs (without c-Myc transduction). Surface phenotype of PSC-derived cells in the stages of MCs and pMCs The myeloid cells (days [13][14] were a heterogeneous population, almost 90% of which was characterized to be CD11b þ ( Fig. 2A) (Fig.…”
Section: Generation Of Pmcs From Mouse Pscsmentioning
confidence: 99%
“…Previous studies have established methods of generating DCs from PSCs, and demonstrated the utility of PSC-derived DCs in cancer immunotherapy (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, generating a large number of DCs from ESCs or iPSCs has required a scaling-up of the initial volume of undifferentiated PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…By genetic engineering, we can generate ES-DCs capable of modulating immune response in an antigen-specific manner. Mouse systems have demonstrated the induction of anti-cancer immunity [6][7][8][9][10] and the prevention of autoimmune disease [11,12] by in vivo administration of genetically engineered ES-DCs.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a new anti-cancer immunotherapy with GPC3 as a target (44)(45)(46)(47), and the phase I clinical trial of GPC3-derived peptide vaccination for advanced HCC is now on going. Because this new immunotherapy is not indicated for ICC, immunohistochemical staining of GPC3 is a useful method to select eligible patients.…”
Section: Discussionmentioning
confidence: 99%